2008
DOI: 10.1089/thy.2008.0055
|View full text |Cite
|
Sign up to set email alerts
|

Intrathyroidal Thymic Tissue Surrounding an Intrathyroidal Parathyroid Gland, the Cause of a Solitary Thyroid Nodule in a 6-Year-Old Boy

Abstract: Ectopic intrathyroidal thymic tissue is a rare occurrence; parathyroid glands sometimes occur in an intrathyroidal location, but this is uncommon. We report a 6-year-old boy who was noted to have a solitary thyroid nodule on ultrasound. A hemithyroidectomy was performed, and histological investigation revealed that the nodule consisted of ectopic intrathyroidal thymus tissue surrounding a well-defined parathyroidal gland. This condition is an exceedingly rare cause of a thyroid nodule, but intrathyroidal thymi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…He reported a fetus with the thymus buried within thyroid and an instance of thymus in a similar location in an infant [11]. Parathyroid glands also have a similar embriyologic origin, and in fact there have been rare cases of IET accompanying or surrounding intrathyroidal parathyroid gland [12,13]. In 1976, Carpenter et al reported 9 cases with thymus inclusions in thyroid glands of 350 children (2.6%) [14].…”
Section: Discussionmentioning
confidence: 99%
“…He reported a fetus with the thymus buried within thyroid and an instance of thymus in a similar location in an infant [11]. Parathyroid glands also have a similar embriyologic origin, and in fact there have been rare cases of IET accompanying or surrounding intrathyroidal parathyroid gland [12,13]. In 1976, Carpenter et al reported 9 cases with thymus inclusions in thyroid glands of 350 children (2.6%) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported an additional patient who underwent thyroid lobectomy because the ectopic thymus was thought to be a tumor [16]. Ectopic intrathyroidal thymus rarely gives rise to symptoms [1,2,3,4,5,6,7]. In the majority of previously reported cases (table 2) the diagnosis of ectopic thymus was made after surgery and/or fine-needle aspiration biopsy because the thymic inclusion was thought to be a thyroid nodule.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of previously reported cases (table 2) the diagnosis of ectopic thymus was made after surgery and/or fine-needle aspiration biopsy because the thymic inclusion was thought to be a thyroid nodule. The differential diagnoses included medullary thyroid carcinoma [1], T-cell non-Hodgkin’s lymphoma [3], benign nodule [5], thyroid carcinoma [4], thyroiditis, and lymphocytic leukemia [6]. On ultrasonography, thymic tissue has a unique appearance and is characterized by a hypoechoic pattern with multiple regular linear and punctate bright echogenicities (bright internal echoes) that represent connective septa and blood vessels within the septa [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications have reported cases of ectopic intrathyroidal thymus that were considered as thyroid nodules, and a fine-needle biopsy or even surgery was performed in order to establish the diagnosis [7,8,14,15]. …”
Section: Discussionmentioning
confidence: 99%